OPERATIONAL EFFICIENCY OF TRANSPORT ENTERPRISES: THE ROLE OF BUSINESS ANALYTICS IN ENSURING COMPETITIVENESS - Редько, Наталія; Левіщенко, Олена; Амеліна, Наталія; Черниш, Олексій (SWorldJournal, 2025)
The article examines the theoretical and applied aspects of operational efficiency of transport enterprises in the context of increasing competition, digital transformation, and dynamic changes in the external environment. The research highlights the key